2012
DOI: 10.1074/jbc.m111.327031
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Functional MicroRNAs in Macrophages with Polarized Phenotypes

Abstract: Background:Macrophages that respond to external stimuli assume a spectrum of activation states. Results: Expression of several miRNAs was altered significantly in different macrophage activation states. Functional activities on cytokine/chemokine expression were shown. Conclusion: miRNAs influenced macrophage differentiation toward distinct activation patterns. Significance: Profiling miRNA guide and passenger strands can reveal miRNA changes in differentiated cells responding to acute stimuli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
320
1
9

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 338 publications
(343 citation statements)
references
References 38 publications
13
320
1
9
Order By: Relevance
“…Recent evidence indicated miR-155 could be an important fine-tuner for the polarization of macrophages (17,24,58). In line with these findings, we also found that macrophages, which expressed decreased levels of miR-155, displayed an M2-like phenotype in ALI mice.…”
Section: Cd4supporting
confidence: 90%
“…Recent evidence indicated miR-155 could be an important fine-tuner for the polarization of macrophages (17,24,58). In line with these findings, we also found that macrophages, which expressed decreased levels of miR-155, displayed an M2-like phenotype in ALI mice.…”
Section: Cd4supporting
confidence: 90%
“…There were consistent changes in several miRNA passenger strands, but surprisingly there were few miRNA guide strands whose abundance changed significantly in these conditions (14). With the exception of miR-193b, the amplitude of change in the abundance of individual guide strands was less than 2-fold (14).…”
mentioning
confidence: 88%
“…36 These miRNAs repress SHIP in Mf and T cells, and consequently induce M2a/ M2c polarization. 37 SHIP is a negative regulator of IL-4-and IL-13-dependent signal transduction. 38 miR-155 induces FOXP3, which plays an important role in Treg cell survival.…”
Section: Ccl1mentioning
confidence: 99%
“…[40][41][42] Quiescent Mf switch to M1Mf in response to bacterial antigens, and subsequently bacterial LPS or efferocytosis stimulates microRNA expression, leading to M2a polarization. 37 Further, M2aMf switch to quiescent Mf in the absence of IL-4, and are reprogrammed to Mf with function to switch to M1Mf in response to TLR agonists. 43 Therefore, M2aMf exist for a relatively short time.…”
Section: Ccl1mentioning
confidence: 99%